Prevention of Criminal Acts of Forgery of Motor Vehicle Owners' Books through Blocking the Electronic Registration Identification (ERI) System - Oki Saputra Syamer; Susi Delmiati (Master of Law Program, Ekasakti University, 2025)
This research is a legal research with descriptive analytical specifications. The blocking action by the West Sumatra Regional Police Directorate as an effort to prevent the misuse of the motor vehicle owner's book is a proactive step in efforts to prevent the misuse of BPKB, especially in the context of violations of the law such as fraud, document forgery, and other criminal acts. The process of blocking action is that the vehicle owner, the police, the leasing institution, or an interested third party (such as a legal institution or court) can apply for a blocking. After receiving the application, the Directorate will verify the completeness and validity of the documents submitted. The block will be recorded in the system. A block can be removed if the legal or administrative issues that led to the block have been resolved. This blocking makes a significant contribution to narrowing the space for criminals who try to use fake BPKB for various illegal acts. Obstacles in preventing the misuse of motor vehicle owners' books with blocking by the West Sumatra Regional Police Directorate are the lack of public knowledge related to the importance of extending vehicle documents, lack of coordination between financing institutions (leasing) and the West Sumatra Regional Police Directorate in reporting vehicle data that must be carried out in the blocking process. This slows down the handling of cases and the removal of blocks for vehicles that have resolved legal or administrative problems. The implementation of the validity of BPKB and the blocking of BPKB must be through the Regident ranmor application system. This happened because the West Sumatra Regional Police Directorate received many cases related to fake BPKB and the leasing party also did not submit a confirmation and block of BPKB at the West Sumatra Regional Police Directorate.